THE EMPLOYEE SUSTAINABILITY STRATEGY IN AUTOMATION - Ilhami, Susanti Dwi; Setiadi, Teguh (Among Makarti, 2023)
Along with the development of existing technology, automation continues to advance rapidly. The implementation of automation implemented by many organizations encourages the emergence of problems, especially among employees. Employee sustainability policies must be considered by the organization. Thus, an in-depth understanding related to employee sustainability is necessary. In this paper, we seek to identify the contribution of employee sustainability for facing automation through as systematic literature review (SLR). Particularly, we systematically: i) the definitions of automation clearly provided, ii) the affect of automation to an organization that implemented automation, iii) the strategy for facing automation by using employee sustainability. The effects of automation could substitute for labor and task not a job. This automation that is implemented by the organization also could create a new job so that it needs a new skill, but the negative affect, it could reduce well-being too. There are two strategies for employee sustainability namely training and work adjustment (adjustments to the organizational environment, work adjustments, adjustments to work superiors, and adjustments to colleagues where employees work). Further, based on our finding for this systematic literature review SLR, we should involve various disciplines such as mechanical engineering, psychology, and human resource management so that the discussion given is more in-depth and comprehensive involving various fields of science.